2000
DOI: 10.1067/mcp.2000.106292
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction between verapamil and almotriptan in healthy volunteers

Abstract: Verapamil modestly inhibited almotriptan clearance to a degree consistent with the modest contribution of CYP3A4 to almotriptan metabolism. This observation and the lack of effect of verapamil on the tolerability to almotriptan administration suggest that no reduction of the almotriptan dose is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Clinical studies have shown that verapamil inhibits the metabolism of CYP3A substrates, such as midazolam, cyclosporin A, simvastatin, buspirone, and almotriptan (Robson et al, 1988;Backman et al, 1994;Kantola et al, 1998;Lamberg et al, 1998;Fleishaker et al, 2000). However, the mechanism of verapamil-mediated drug interactions has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that verapamil inhibits the metabolism of CYP3A substrates, such as midazolam, cyclosporin A, simvastatin, buspirone, and almotriptan (Robson et al, 1988;Backman et al, 1994;Kantola et al, 1998;Lamberg et al, 1998;Fleishaker et al, 2000). However, the mechanism of verapamil-mediated drug interactions has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The N-demethylation and N-oxidation of the dimethylaminoethyl group are minor metabolic reactions both in vitro and in vivo. Different clinical trials conducted to study the effect of CYP3A4, CYP2D6, and MAO-A on the pharmacokinetics of almotriptan showed that verapamil and fluoxetine modestly inhibited almotriptan clearance, a result consistent with the assignement of CYP3A4 and CYP2D6 as the enzymes responsible for the oxidation of the pyrrolidine moiety (Fleishaker et al, 2000(Fleishaker et al, , 2001a. Moreover, moclobemide increased plasma concentrations of almotriptan by 37%, thus confirming that oxidative deamination of almotriptan by MAO-A was the major route of metabolism and that the degree of interaction was much less than that seen previously for sumatriptan, rizatriptan, or zolmitriptan given with moclobemide (Fleishaker et al, 2001b).…”
mentioning
confidence: 79%
“…Therefore, CYP 3A4 inducers and inhibitors are likely to result in decreased and increased plasma levels of verapamil, respectively [3032]. Co-medication with other drugs indicated in CH such as triptans, prednisolone or ergotamine, which are also metabolized by CYP 3A4, could induce a drug–drug interaction with verapamil [33, 34]. Verapamil is also a probe inhibitor of transporter P-glycoprotein (P-gp).…”
Section: Discussionmentioning
confidence: 99%